Development of semitransparent CIGS thin-film solar cells modified with a sulfurized-AgGa layer for building applications. Issue 27 (23rd June 2016) - Saifullah, Muhammad; Ahn, SeJin; Gwak, Jihye; Ahn, Seungkyu; Kim, Kihwan; Cho, Junsik; Park, Joo Hyung; Eo, Young Joo; Cho, Ara; Yoo, Jin-Su; Yun, Jae Ho
Abstract : The insertion of sulfurized-AgGa layer at CIGS/ITO interface reduced the bulk and back surface recombination and thus ameliorated the PV performance without adversely affecting the cell's visible transmittance. Abstract : Different from conventional photovoltaics, building-integrated photovoltaics needs not only high performance but also a high degree of transparency. Nevertheless, the Cu(In, Ga)Se2 (CIGS) solar cell has advantages in terms of the highest conversion efficiency and stability among all thin-film-based solar cells. The semitransparent (ST) CIGS solar cell using an ultrathin CIGS absorber on a transparent conducting oxide (TCO) experiences loss in fill factor and open circuit voltage due to the poor grain morphology and CIGS/TCO interface. Thus, these issues must be addressed to realize ST CIGS solar cells. Wide-bandgap (1.5 eV) submicron CIGS-based solar cells were prepared in this study unlike conventional CIGS with a bandgap of 1.2 eV, in order to enhance see-throughness. But such cells demonstrated low conversion efficiency due to the poor grain morphology and absence of back grading. Therefore, for the sake of improving grain morphology and to create back grading, a sulfurized-AgGa (AGS) layer was deposited between CIGS and the indium tin oxide (ITO) back contact. Ag from the AGS layer diffused throughout the absorber and thus ameliorated the grain morphology. However, Ga and S in the AGS layer remained confined near the back contact, therefore resulting in the creation of back grading. Consequently, a solar cell based on 230 nm thick CIGS modified with a 45 nm thick AGS layer exhibited efficiency of 5.94% with averaged visible transmittance over 25%. This is the highest reported efficiency for a ST CIGS solar cell with over 20% visible transparency. The CIGS solar cell based on this novel approach can be a competent candidate for building-integrated semitransparent photovoltaics applications.